Flipping the classroom with a LMS: Designing a technologybased learning model - Zamzami Zainuddin; Hardika Dwi Hermawan; Febritesna Nuraini; Santo Mugi Prayitno; Taufik Probowasito (Journal of Education and Learning (EduLearn), 2019)
This study proposes to present a sample design of a flipped learning instructional model for teaching Islamic Studies course at an Indonesian higher education institution. A bottom-up flipped learning model was developed in this study, based on Bloom’s taxonomy of educational objectives. A Learning Management System (LMS), Schoology, was employed as a platform to share pre-class video lectures for student learning activities outside-of-class. Three main activities proposed by the researchers outside of the class activities, namely, Watching, Summarizing, and Notetaking (WSN), whereas give and take conversation is the main class activity. This study implies that the bottom-up flipped learning model could potentially be implemented for teaching Islamic studies course in Indonesian higher education institutions, with the aim of fostering students' highest level of cognitive domains and independent learning skills. This study has implications for the Ministry of Research, Technology, and Higher Education and the Ministry of Religious Affairs of the Republic of Indonesia or policymakers to consider the flipped classroom as a contemporary teaching model for teaching Islamic studies course and other subjects at any in Indonesian higher education institutions.